2015
DOI: 10.4103/0366-6999.160562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Danggui-Shaoyao-San on the Influence of Spatial Learning and Memory Induced by Experimental Tooth Movement

Abstract: Background:The pain caused by orthodontic treatment has been considered as tough problems in orthodontic practice. There is substantial literature on pain which has exactly effected on learning and memory; orthodontic tooth movement affected the emotional status has been showed positive outcomes. Danggui-Shaoyao-San (DSS) is a Traditional Chinese Medicine prescription that has been used for pain treatment and analgesic effect for orthodontic pain via inhibiting the activations of neuron and glia. We raised the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…An animal study found that orthodontic pain could impair memory and learning through inducing hippocampal neuron apoptosis. 18 , 97 This finding was reinforced by another study in which chronic pain was revealed to interfere with memory formation in the hippocampus. 98 This effect of pain on the hippocampus may be a built-in strategy to alleviate chronic pain, but the effect on orthodontic pain in humans need to be validated in future studies.…”
Section: Neural Circuits and Regulation Of Orthodontic Painmentioning
confidence: 81%
See 1 more Smart Citation
“…An animal study found that orthodontic pain could impair memory and learning through inducing hippocampal neuron apoptosis. 18 , 97 This finding was reinforced by another study in which chronic pain was revealed to interfere with memory formation in the hippocampus. 98 This effect of pain on the hippocampus may be a built-in strategy to alleviate chronic pain, but the effect on orthodontic pain in humans need to be validated in future studies.…”
Section: Neural Circuits and Regulation Of Orthodontic Painmentioning
confidence: 81%
“…Animal studies have indicated that orthodontic pain results in emotional stress 17 and transient learning and memory deficits. 18 …”
Section: Characteristics Of Orthodontic Painmentioning
confidence: 99%
“…[ 31 ] Furthermore, DSS has shown potential in enhancing learning and memory abilities in female diabetic mice (db/db) and senescence-accelerated mice (SAM), likely by increasing the levels of estradiol (E2), nitric oxide (NO), and glycine. [ 32 33 ] The active ingredient in DSS, Z-ligustilide, has been associated with increased levels of neurosteroids, pregnenolone, and allopregnanolone, in brain tissue. [ 34 ] Intriguingly, previous network pharmacology studies have suggested that DSS might exert neuroprotective effects after stroke by modulating the steroid hormone signaling pathway and steroid hormone receptor activity, as evidenced by GO functional enrichment analysis and KEGG pathway enrichment analysis.…”
Section: Danggui-shaoyao-san’s Role In Neurosteroid Regulationmentioning
confidence: 99%